Assessment of genetic relationships within Bouea (Anacardiaceae) accessions in Peninsular Malaysia using inter simple sequence repeats (ISSR) markers - Ghazali, Mohd Norfaizal; Yunus, Muhamad Fahmi; Mohammad, Abdul Latiff (African Journal of Biotechnology, 2015)
Malaysia is a genetically diverse hotspot for wild relatives of Mangifera and other Anacardiaceae members. The genus Bouea is interesting in that it has small sweet-sour edible fruits. This genus consists of two species, namely Kundang (Bouea macrophylla) and Remia (B. oppositifolia) which are of economic value. In this study, we highlighted the molecular evidences using inter simple sequence repeats (ISSR) markers to understand its genetic relatedness among accessions. A total of 52 ISSR have been screened on selected accession of Kundang and Remia from Peninsular Malaysia. Ten of the 52 primers for Kundang generated 89 scorable bands, where 45 bands (50.2%) were polymorphic. The simple matching coefficient of similarity provided similarity values ranging from 0.659 to 0.955 while relationship among the different accessions was distributed among three main divergent clusters. For Remia, 10 of the 52 primers tested gave 89 scorable bands, where 54 bands (59.5%) were polymorphic. The simple matching coefficient of similarity values ranged from 0.591 to 0.977 while the cluster analysis separated 23 accessions into two well-defined clusters. These studies indicate that there was considerable ISSR variation among the accessions reflecting variation among the accessions, which were morphologically indistinguishable. DNA polymorphism detected by ISSR analysis offers a useful molecular marker for the identification of different accessions of Kundang and Remia.